Enhanced Immune Responses by Virus-Mimetic Polymeric Nanostructures Against Infectious Diseases - Li, Xinpei; Liu, Shengqiu; Yin, Panchao; Chen, Kun (Frontiers in Immunology, 2022)
Intermittent outbreaks of global pandemic disease have spurred new sensors and medicines development for the prevention of disease spread. This perspective specifically covers recent advances, challenges, and future directions in virus-mimetic polymeric nanostructures and their application in biological medicines with a special emphasis on subunit vaccine development. Polymers, with their tailorable compositions and properties, facilitate the ingenious design of various polymeric nanostructures. As one type of polymeric nanostructures, virus-mimetic polymeric nanostructures have been developed as an attractive platform for enhanced immune responses, since they combine the merits of polymer nanocores with the biomimetic characteristic of virus which displays multivalent epitopes on their surfaces. This perspective also provides an applicative approach to rationally design virus-mimetic polymeric platform based on nanostructures that are self-assembled by using polymers as templates and the antigens and metal oxide clusters loaded on their surface to mimic viruses in size and surface antigenicity. Sub-200 nm virus-mimetic polymeric nanostructures are in a relatively lower level of endotoxins and can promote the antigens to elicit potent humoral and cellular immune response against pathogenic bacteria. The promising development of virus-mimetic polymeric nanostructures will continue to protect human health from common pathogens and emerging infectious threats.